Sam : a novel - Goodman, Allegra (The Dial Press, 2023)
"There is a girl, and her name is Sam. She adores her father, though he isn't around much. Her mother, Courtney, struggles to make ends meet, and never fails to remind her daughter that her life should be different. Sam doesn't fit in at school, where the other girls have the right shade of blue jeans and don't question the rules. Sam doesn't care about jeans or rules. She just loves to climb--trees, fences, walls, the side of a building. When she's climbing, she discovers a place she belongs: she can turn off her brain, pain has a purpose, and it's okay if you want to win. As Sam grows into her teens, she grapples with self-doubt and insecurity for the first time. She yearns for her climbing coach to notice her, but his attention crosses boundaries she doesn't know how to resist. She wishes her father would leave for good, instead of always coming and going, but once he's gone, she realizes how much she's lost. She rages against her mother's constant pressure to plan for a more secure future, but also sees how hard she works and how much she sacrifices. Wrestling with who she wants to be in the face of what she's expected to do, Sam comes to understand that she alone can make her dreams come true"--